2015
DOI: 10.1016/j.immuni.2015.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Complement Regulates Nutrient Influx and Metabolic Reprogramming during Th1 Cell Responses

Abstract: SummaryExpansion and acquisition of Th1 cell effector function requires metabolic reprogramming; however, the signals instructing these adaptations remain poorly defined. Here we found that in activated human T cells, autocrine stimulation of the complement receptor CD46, and specifically its intracellular domain CYT-1, was required for induction of the amino acid (AA) transporter LAT1 and enhanced expression of the glucose transporter GLUT1. Furthermore, CD46 activation simultaneously drove expression of LAMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
305
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 213 publications
(332 citation statements)
references
References 57 publications
(100 reference statements)
6
305
0
6
Order By: Relevance
“…Finally, our data and other recent investigations now broaden the role of the newly discovered ICS (4,11). The finding of a C3(H 2 O)-recycling pathway has important implications for our understanding of basic processes the cell utilizes for homeostasis and defense.…”
Section: Methodssupporting
confidence: 64%
See 3 more Smart Citations
“…Finally, our data and other recent investigations now broaden the role of the newly discovered ICS (4,11). The finding of a C3(H 2 O)-recycling pathway has important implications for our understanding of basic processes the cell utilizes for homeostasis and defense.…”
Section: Methodssupporting
confidence: 64%
“…Further, CTSLdriven C3a generation is required for CD4 + T cell survival, and shuttling of C3a to the cell surface is necessary for Th1 effector cell differentiation and proinflammatory cytokine production (4). In a follow-up to this study, the Kemper group demonstrated that intracellular C3b generation (and autocrine CD46 stimulation) is required for metabolic reprogramming that allows Th1 cell activation and contraction (11). Further, this group suggested that such reprogramming also provides for a novel "complement-metabolism-inflammasome" axis (12).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…The extent to which FAO occurs in effector T cells is likely to be highly context dependent, in part due to the heterogeneity of this population of cells during an immune response. Studies using animal models of graft versus host disease (GvHD) have found that alloreactive T cells increase fatty acid uptake and enhance FAO compared with other effector T cells (Gatza et al, 2011;Byersdorfer et al, 2013;Glick et al, 2014). Suppressing Akt during activation can induce a metabolic profile suggestive of FAO utilization (Crompton et al, 2015), and culturing CD8 effector T cells in low glucose enhances FAO .…”
Section: Reviewmentioning
confidence: 99%